주민인식에 기반한 아파트단지 내 수경시설 이용 영향 요인 분석 - 계획·설계, 유지·관리, 이용 행태를 중심으로 - 박도환; 조세환; Park, Do-Hwan; Cho, Se-Hwan (한국조경학회지, 2017)
This study analyzes the multiple effects of the following three aspects of waterscape facilities within apartment complexes: planning/designing, maintenance/management, and use of the facilities and suggests primary documents that will be fundamental for the methods to accelerate the implementation of waterscape facilities. A survey and analysis was conducted among a few of the most representative private apartment complexes in Seoul in accordance with the management and operation of waterscape facilities. The analysis used frequency analysis, descriptive statistics, reliability test, t-test, and PLS regression analysis. The research findings are as follows: first, the degree of use of waterscape facilities was found to be low regardless of the levels of operation, but residents' preference for the facilities was shown to be high, thus indicating there are still high expectations on the part of residents. Second, regardless of whether the facilities are being operated efficiently, the two items of location and display method under the section of planning and designing and the two items of aptitude and convenience under the section of use were found to positively affect the operation and use of waterscape facilities. Particularly, the item of freshness, cleanliness was shown to be directly and indirectly correlated with obsolescence, administration costs, and noise, which negatively affect the operation. Third, it was found that the administration costs itself that had been shown as the most negative factor of operating landscaping facilities in previous research did not cause problems in the residential area where the facilities are not operated efficiently. The finding suggests that the administration costs do not matter but that in the case of experience- and entertainment-typed facilities that residents want, they are linked to problems that do not introduce the desired facilities. Fourth, it was found that various aspects of planning, designing, maintaining, and using facilities interconnect and affect one another in the process of operating and using waterscape facilities resulting in the need to have a comprehensive approach to these three factors of planning, design, maintenance, management, and utilization. This study proposes that the needs and values of residents should be reflected to activate the introduction of landscaping facilities in the apartment complexes. 본 연구는 아파트단지 내 수경시설의 계획 설계, 유지 관리, 이용 행태 등 요소가 복합적으로 수경시설의 운영 및 이용에 어떠한 영향을 미치는지를 분석함으로써 향후 아파트단지 내 수경시설 도입 활성화 방안 마련을 위한 기초자료 제시를 목적으로 수행하였다. 본 연구는 수경시설 관리 및 운영 정도 등 기준에 따라 서울지역 대표적 민간 아파트 4개소를 대상으로 앙케이트 조사방법을 통해 연구를 수행되었으며, 분석에는 빈도분석, 기술통계분석, 신뢰도분석, t검정, PLS 회귀분석 등의 방법이 사용되었다. 연구의 결과는 다음과 같다. 첫째, 전반적으로 수경시설은 운영성 여부에 관계없이 이용도는 낮게 나타나고 있지만, 선호도는 높게 나타나고 있어, 수경시설에 대한 주민의 기대치는 여전히 높은 것으로 나타났다. 둘째, 수경시설의 운영이 잘 되는 주거단지든 아니든 간에 계획 설계 요소에서는 '위치'와 '연출기법' 등 2개 항목, 이용 행태 요소에서는 '쾌적성'과 '편리성' 등 2개 항목 등 모두 4개 항목이 수경시설의 운영 및 이용에 긍정적인 영향을 미치는 것으로 나타났다. 특히, 이들 중 '쾌적성' 항목은 수경시설 운영 및 이용에 부정적인 영향을 미치는 '노후정도', '고장유무', '관리비', '소음' 항목과 직 간접적인 연관이 있는 것으로 나타났다. 셋째, 기존의 연구들에서 수경시설의 운영에 가장 부정적 요인으로 나타난 '관리비' 요인은 수경시설의 운영이 잘 되지 않는 주거단지에서 오히려 문제성을 느끼지 않는 것으로 나타나, 특이성을 띄었다. 즉, 관리비 자체가 문제가 되는 것으로 인식하고 있는 것이 아니라, 체험형이나 유희형과 같은, 주민이 원하는 수경시설을 도입하지 않는 문제와 연계되어 있는 것으로 나타났다. 마지막으로 수경시설의 운영 및 이용에는 계획 설계, 유지 관리, 이용 행태의 요소들이 상호 복합적으로 연관되어 영향을 끼치고 있는 것으로 나타남으로써 이들 3개 요소에 대한 포괄적 접근이 필요하다는 결과를 얻을 수 있었다. 이상의 결과에서 향후 아파트단지 수경시설 도입의 활성화를 위해서는 계획 설계, 유지 관리, 이용 행태 요소를 고려한 종합적 접근과 함께 특히, 수경시설의 프로그램 등에서 주민의 욕구와 가치 등 인식이 반영되어야 할 것으로 제안되었다.